Asuhan Keperawatan pada Tn. I dengan Diagnosis Medis Efusi Pleura di Rumah Sakit Umum Pusat H. Adam Malik : Case Report - Syah Fara Dillasani Sirait; Mula Tarigan; Dina Afriani (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Pleural effusion is a pathological condition characterized by the accumulation of fluid in the pleural cavity, which can cause shortness of breath, chest pain, and other complications. This study aims to evaluate evidence-based nursing care for patients diagnosed with pleural effusion using a case report approach. The assessment was conducted holistically, including interviews, observations, and physical examinations. The results show that nursing interventions combining respiratory physiotherapy, such as breathing exercises, mobilization, and patient education, along with medical care, are effective in reducing shortness of breath and improving chest expansion in patients. The management of pleural effusion involves a multidisciplinary approach, including early diagnosis through thoracentesis and imaging, as well as supportive therapies such as respiratory physiotherapy, pleural fluid drainage, and medical interventions tailored to the underlying etiology. This study also highlights the critical role of respiratory physiotherapy in accelerating patient recovery, including deep breathing exercises, chest mobilization, and posture correction. The evaluation indicates that, although the patient’s respiratory problems were not completely resolved, there was significant improvement in overall health status. This study underscores the importance of applying a multidisciplinary approach to improve the quality of life for patients with pleural effusion.